DAMPAK PENGGUNAAN AIR BERSUHU EKSTRIM TERHADAP KEKUATAN TEKAN BETON - Syarifuddin, Syarifuddin (FORUM BANGUNAN, 2015)
The study aimed to compare the compressive strength and unit weight of normal concrete with concrete using extreme temperature wate, cold water temperature is + 0 °C and hot water temperature is + 100 °C. As a comparison sample used normal concrete using water temperature + 4 °C. The composition of the concrete mix is volume ratio 1:2:3 and the amount of concrete cube specimen every 15 cubes, a total of three kinds of concrete sample; NC, CC and HC. Specimens used were 150 mm concrete cube. Measurement of unit weight using the balance sheet and compressive strength testing using a Universal Testing Machine capacity of 100 tons. The results showed an average unit weight at 28 days of the concrete samples NC, CC and HC, respectively 2151.11 kg/m3, 2210,37 kg/m3 and 2121,48 kg/m3. Average compressive strength at 28 days, respectively kg/m2 106.05, 104.39 and 167.69 kg/m2 with a maximum compressive strength of 181.76 kg/m2 in concrete using hot water.